2014
DOI: 10.7897/2230-8407.0512183
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Antihypertensive Agents Among Hypertensive Patients of Nepal

Abstract: These investigations compare the effectiveness of antihypertensive agents among hypertensive patients. It was an open label, prospective and comparative study carried out in the Out-patient department at BPKIHS, Dharan, Sunsari, Nepal. Patients of either sex aged between 25-80 years suffering from mild to moderate hypertension were randomly selected. In this study indicate various types of antihypertensive drugs for the management of hypertension like Calcium channel blockers (amlodipine), Angiotensin Converti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…In the present study, there was male preponderance in patients having HTN with diabetes (54% [17,20,[22][23][24]. This could probably be due to significantly higher awareness, treatment, and control rates among women than men as supported by a recent data from the 2007 to 2010 National Health and Nutrition Examination Survey [25].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In the present study, there was male preponderance in patients having HTN with diabetes (54% [17,20,[22][23][24]. This could probably be due to significantly higher awareness, treatment, and control rates among women than men as supported by a recent data from the 2007 to 2010 National Health and Nutrition Examination Survey [25].…”
Section: Discussionsupporting
confidence: 63%
“…However, most of the other studies had shown an inconsistent finding with the present study in relation to the most common 2-drug combination drugs prescribed. Tamuno and Fadare and Pandaya et al reported that the most commonly used 2-drug combination was CCB + diuretic (12% and 37.8%, respectively) [23,28]. According to Kausalya et al, ACE inhibitor + CCB was the most commonly prescribed 2-drug combination, whereas in a study by Jaganan et al, ACE inhibitors…”
Section: Discussionmentioning
confidence: 99%
“…Among two drug regimen CCB+ Diuretics combination are generally prescribed. Similarly, Pandaya et al found that the most generally prescribed two-drug combination was CCB+ Diuretic (12 percent and 37.8%, respectively) 8 . In this study, 32.07 percent (n=34) of the participants were administered a three-drug antihypertensive medication regimen.…”
Section: Who Prescribing Indicators?mentioning
confidence: 89%